Stream Water and Groundwater Interaction Revealed by Temperature Monitoring in Agricultural Areas - Youngyun Park (Water, 2013)
Variations in stream water, streambed, adjacent stream sediment, and groundwater temperatures in the Haean basin, Korea were examined using time series analyses including auto-correlation, spectral density, and cross-correlation functions. The temperatures of the ambient air, stream water, streambed (depth = 10 cm), and adjacent stream sediment (depth = 10 cm) showed distinctive diurnal variations with long-term seasonal cooling trends, while groundwater temperature showed only a seasonal decreasing trend with little diurnal variations. Auto-correlations and spectral densities of the stream water, streambed, and sediment temperatures also revealed strong daily cyclical behaviors, with longer periodic cycles varying from weekly to monthly. Amplitudes and lag times of the streambed thermal signals were also affected by the hydraulic conductivities of the sediments. Lower hydraulic conductivity indicates a more attenuated and slower thermal response for the streambed. The calculated vertical water flow velocities of the streambed revealed that the investigated stream locations were under losing or gaining conditions, depending on the location and time.